Examining the Role of Training, Compensation, and Work Environment in Employee Performance: A Gender-Based Analysis - Krisnadayanti, Betty; Subiyanto , Didik; Purnamarini, Tri Ratna; Lada, Suddin (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This study aims to analyze the influence of training, compensation, and work environment on employee performance by considering gender differences as a moderating variable. The study seeks to determine the extent to which these factors contribute to performance enhancement among male and female employees at PT POS Indonesia DIY. Design/methodology/approach: A quantitative research approach was employed using the Multi-Group Analysis (MGA) method in Structural Equation Modeling (SEM). The study was conducted on a population comprising all employees of PT POS Indonesia DIY, with a sample of 117 respondents selected through random sampling. Data were collected via a Likert scale-based questionnaire, measuring key indicators of training, compensation, work environment, and employee performance. Research Findings: The findings indicate that the work environment plays a dominant role in improving employee performance, whereas training has a limited impact, and compensation does not significantly influence performance. When analyzed by gender, the results reveal that for male employees, only the work environment has a strong effect on performance, while training and compensation are insignificant. In contrast, for female employees, training has a weak effect, compensation remains insignificant, and the work environment continues to be the key determinant of performance. Theoretical Contribution/Originality: This study contributes to the literature on employee performance by providing empirical evidence on the differential impact of training, compensation, and work environment across gender groups. The findings highlight the necessity of prioritizing a conducive work environment to enhance productivity, as well as the importance of considering gender-specific responses when designing organizational policies. From a managerial perspective, optimizing work facilities and fostering a supportive organizational culture are critical strategies for improving employee performance.